Flow cytometry is of limited utility in the early identification of "Double‐hit" B‐cell lymphomas1. Issue 3 (22nd January 2013) - Platt, Mia Y.; DeLelys, Michelle E.; Preffer, Frederic I.; Sohani, Aliyah R.
Abstract: Background: B‐cell lymphomas with concurrent translocations of MYC and BCL2 or BCL6, also known as "double‐hit" lymphomas (DHL), are rare malignancies characterized by aggressive clinical behavior and poor prognosis. Previous reports suggest that decreased CD20 and/or CD19 expression by flow cytometry is relatively common in DHL and may help to identify cases requiring additional cytogenetic analysis. Methods: We conducted a retrospective analysis of 26 cases of DHL, and compared their flow cytometric characteristics to cases of Burkitt lymphoma (BL) and diffuse large B‐cell lymphoma (DLBCL). Cases were analyzed by four‐color flow cytometry, and bivariate dot‐plots were reviewed for light scatter characteristics, CD19, CD20, CD45, and surface light chain. Results: Relatively few DHL cases showed dim expression of CD19 or CD20, and statistically significant differences were found only in the frequency of dim CD19 expression between DHL and BL or DLBCL. Although concomitant dim CD19 and CD20 expression was exclusive to DHL, it was present in only a minority of cases. Conclusions: We conclude that although a subset of DHL expresses aberrant levels of CD19 and/or CD20 by flow cytometry, these findings are of limited utility in identifying cases requiring cytogenetic analysis due to their low frequency. Until more sensitive pathologic parameters can be identified and validated, the decision to perform cytogenetic analysis should rest on a combination of clinical, morphologic, and immunophenotypic features suggestive of high‐grade, aggressive disease. © 2013 International Clinical Cytometry Society